Clinical and ultrasonographic predictors for achieving minimal disease activity in patients with psoriatic arthritis: the UPSTREAM (Ultrasound in PSoriatic arthritis TREAtMent) prospective observational study protocol. Issue 7 (10th July 2018) - Canzoni, Marco; Piga, Matteo; Zabotti, Alen; Scirè, Carlo Alberto; Carrara, Greta; Olivieri, Ignazio; Iagnocco, Annamaria
Abstract : Introduction: Psoriatic arthritis (PsA) occurs in 10%–15% of people with psoriasis and accounts for 10%–20% of early arthritis clinics referral. Only a few prognostic factors of therapeutic response in patients with PsA have been identified. In the last years, the role of imaging has grown up and the European League Against Rheumatism recognised that ultrasound (US) has higher sensitivity than clinical examination to detect inflammatory disease activity. The aims of the Ultrasound in PSoriatic arthritis TREAtMent (UPSTREAM) study are to integrate clinic and US in order to inform whether US has provide an added prognostic value in PsA. Methods and analysis: UPSTREAM is an observational prospective cohort study enrolling patients with PsA having clinically active joint disease and starting a new course of therapy. The primary objective is to evaluate the additional value of US over clinical examination in detecting patients achieving minimal disease activity after 6 months. Data will be obtained at baseline and at standard clinical follow-up visits. Patient's clinical assessment will be performed according to the core set proposed by the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis-Outcome Measures in Rheumatology. Sonographic evaluations will be performed by expert sonographers in 42 joints, 36 tendons, 12 entheses and 2 bursae, according to a score that will be purposely developed for PsA by the US Study Group of the Italian Society for Rheumatology. The UPSTREAM study will identify clinical and US predictors of response to treatment in patients with PsA and active peripheral arthritis starting a new course of therapy. Ethics and dissemination: Ethic approval for this study has been obtained from the institutional review board (IRB)/independent ethics committee (IEC) Comitato Etico Lazio 1 (Prot. N 198 02-02-2017) and then locally from the IRB/IEC of each participating centre. Results will be published in relevant scientific journals and be disseminated in international conferences. Fully anonymised data will be accessible from authors upon request. Trial registration number: NCT03330769; Pre-results .